2022
DOI: 10.7717/peerj.13753
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the composition and diversity of gut microbiota in white-lipped deer (Cervus albirostris)

Abstract: The gut microbiota has key physiological functions in host adaptation, although little is known about the seasonal changes in the composition and diversity of the gut microbiota in deer. In this study, seasonal variations (grassy and withering season) in the gut microbiota of white-lipped deer (Cervus albirostris), which lives in alpine environments, were explored through 16S rRNA high-throughput sequencing based on sixteen fecal samples collected from Gansu Qilian Mountain National Nature Reserve in China. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…In this study, Firmicutes and Bacteroidota were the dominant phyla in Père David’s deer from different living conditions, consistent with previous conclusions in this endangered species ( Sun et al, 2019 ). Previous studies have shown that the gut microbiota of ruminants e.g ., white-lipped deer ( Cervus albirostris ) ( Li et al, 2022 ; You et al, 2022 ), forest musks ( Moschus berezovskii ) ( Zhao et al, 2021 ), alpine musks ( Moschus sifanicus ) ( Jiang et al, 2021 ), and blue sheep ( Pseudois nayaur ) ( Zhu et al, 2020 ), were predominantly made up by Firmicutes and Bacteroidota. This was mainly because ruminants are herbivores that need microorganisms to help them digest and absorb nutrients from plants ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Firmicutes and Bacteroidota were the dominant phyla in Père David’s deer from different living conditions, consistent with previous conclusions in this endangered species ( Sun et al, 2019 ). Previous studies have shown that the gut microbiota of ruminants e.g ., white-lipped deer ( Cervus albirostris ) ( Li et al, 2022 ; You et al, 2022 ), forest musks ( Moschus berezovskii ) ( Zhao et al, 2021 ), alpine musks ( Moschus sifanicus ) ( Jiang et al, 2021 ), and blue sheep ( Pseudois nayaur ) ( Zhu et al, 2020 ), were predominantly made up by Firmicutes and Bacteroidota. This was mainly because ruminants are herbivores that need microorganisms to help them digest and absorb nutrients from plants ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the gut microbiota of wild animals is related to host species, their diet, and environmental changes such as seasons 62 , and it is also crucial for maintaining health condition of its host 63 . Therefore, analyzing the gut microbiota of wild animals has been proposed as a conservation tool for wildlife, including endangered species [64][65][66] .…”
Section: Discussionmentioning
confidence: 99%
“…Food resources can change over temporal scales. For the deer population, sufficient and diverse fresh plant-derived food is available in the grassy season; however, food resources and choices are relatively limited in the withering season due to severe weather conditions ( Hu et al, 2018 ; Li et al, 2022 ; Su et al, 2022 ; You et al, 2022 ). Dramatic seasonal variations in gut microbiota compositions are observed in deer species ( Figure 1A ).…”
Section: Effects Of Diets On the Gut Microbiota Of Deer Speciesmentioning
confidence: 99%
“…Beneficial microbe administration-based microbiota manipulation approaches mentioned below have consequently been developed and have shown promising benefits in animal breeding and raising practices ( Anee et al, 2021 ). With such rapid developments in omics technologies and their contributions to microbiota decryption and application, several omics-based studies have been conducted for analyzing the gut microbiota of deer species, particularly six species belonging to the family Cervidae [sika deer ( C. nippon ) ( Guan et al, 2017 ; Wang et al, 2022 ), Père David’s deer ( E. davidianus ) ( Zhang et al, 2018 ; Sun et al, 2019 ), red deer ( C. elaphus ) ( Menke et al, 2019 ; Wang et al, 2019 ), white-lipped deer ( C. albirostris ) ( Li J. G. et al, 2017 ; Li et al, 2022 ; You et al, 2022 ), Siberian roe deer ( Capreolus pygargus ) ( Liu J. et al, 2019 ), and white-tailed deer ( Odocoileus virginianus )] ( Delgado et al, 2017 ; Minich et al, 2021 ) and three species belonging to the genus Moschus [alpine musk deer ( M. chrysogaster ) ( Sun et al, 2020 ), Siberian musk deer ( M. moschiferus ) ( Su et al, 2022 ), and forest musk deer ( M. berezovskii )] ( Li Y. et al, 2017 ). The predominant bacterial phyla in these deer species were found to be Firmicutes , Bacteroidetes , Proteobacteria , and Actinobacteria ; these findings are consistent with previous findings regarding the gut microbiota of ruminants ( Tanca et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%